2014
DOI: 10.1261/rna.047084.114
|View full text |Cite
|
Sign up to set email alerts
|

Initiation codon selection is accomplished by a scanning mechanism without crucial initiation factors in Sindbis virus subgenomic mRNA

Abstract: Translation initiation of alphavirus subgenomic mRNA (sgmRNA) can occur in the absence of several initiation factors (eIFs) in infected cells; however, the precise translation mechanism is still poorly understood. In this study, we have examined the mechanism of initiation and AUG selection in Sindbis virus (SINV) sgmRNA. Our present findings suggest that sgmRNA is translated via a scanning mechanism, since the presence of a hairpin structure before the initiation codon hampers protein synthesis directed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…The essential components of the cap-dependent translation initiation machinery, EIF4A1 and EIF4E, were not stimulated by the infection in spite of the activation of their protein partner EIF4G1 (Table S1). This agrees with previous data showing that these two initiation factors do not participate in SINV sgRNA translation (Carrasco et al, 2018; Castello et al, 2006; Garcia-Moreno et al, 2015; Garcia-Moreno et al, 2013). A recent report showed that EIF3D is a cap-binding protein that substitutes EIF4F in the translation of specific mRNA pools (Lee et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…The essential components of the cap-dependent translation initiation machinery, EIF4A1 and EIF4E, were not stimulated by the infection in spite of the activation of their protein partner EIF4G1 (Table S1). This agrees with previous data showing that these two initiation factors do not participate in SINV sgRNA translation (Carrasco et al, 2018; Castello et al, 2006; Garcia-Moreno et al, 2015; Garcia-Moreno et al, 2013). A recent report showed that EIF3D is a cap-binding protein that substitutes EIF4F in the translation of specific mRNA pools (Lee et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…Of note, there was a substantial inhibition in the synthesis of C protein in insect cells (∼70%) with replicons bearing AUG or CUG (Fig. 7C,E), likely because melting of this DSH variant is hampered by insect ribosomes as was described previously (Garcia-Moreno et al 2015). After 7 h, cells were collected in loading buffer and extracted proteins were analyzed by western blotting with an anti-C antibody.…”
Section: Structure-activity Relationship Of Dsh In Signaling the Initmentioning
confidence: 52%
“…This aminoacyl-tRNA is then translocated to the P site mediated by eEF2 in a GTP-dependent process. We have previously advanced the idea that some similarities exist between the mechanism of initiation directed by IGR CrPV and the alphavirus sgRNA (Garcia-Moreno et al 2015;Sanz et al 2017;Carrasco et al 2018).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations